Organoleptic Characteristics of Food Bars with Substituted Tempeh and Tofu Waste as Snacks for Obese Adolescents - Panjaitan, Raini; NST, Nadiyah Azhar; Ulina Sitepu, Sari Desi Esta; Sitepu, Abdi Lestari; Sipayung, Selamat Tuahta (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2024)
The nutritional issues among adolescents included both undernutrition and overnutrition. Undernutrition was generally caused by low energy intake from food compared to the energy burned by the body, while overnutrition occurred when energy intake exceeded energy expenditure. These nutritional problems also influence adolescents' body image. This research aimed to develop food bar products made from tempeh and tofu waste as snacks for obese adolescents. The research process began with the preparation stage of raw materials, including drying tofu waste. Subsequently, food bars were made using three formulas: F1 (60% dried tofu waste and 40% tempeh), F2 (70% dried tofu waste and 30% tempeh), and F3 (80% dried tofu waste and 20% tempeh). The third stage involved organoleptic testing with 30 untrained panelists, using a preference test for attributes of texture, color, aroma, and taste, with a hedonic scale ranging from 1 (dislike extremely) to 4 (like extremely). Statistical analysis was conducted using ANOVA and Duncan's Test with a confidence level of 95%. The results showed that the panelists preferred food bar product F3 based on texture, color, and aroma attributes, while, F1 received the highest rating. Overall, F3 was deemed the most favored. The conclusion of this study indicated that the recommended food bars as snacks for obese adolescents were F3 (80% dried tofu waste and 20% tempeh), with an average liking score of 3 (like).